Reduced DNA polytenization of a minichromosome region undergoing position-effect variegation in Drosophila. - Karpen, G.H.; Spradling, A.C. (Cell, 1990)
Molecular analysis of a Drosophila minichromosome, Dp(1;f)1187, revealed a relationship between position-effect variegation and the copy number reductions of heterochromatic sequences that occur in polytene cells. Heterochromatin adjacent to a defined junction with euchromatin underpolytenized at least 60-fold. Lesser reductions were observed in euchromatic sequences up to 103 kb from the breakpoint. The copy number changes behaved in all respects like the expression of yellow, a gene located within the affected region. Both copy number and yellow expression displayed a cell-by-cell mosaic pattern of reduction, and adding a Y chromosome, a known suppressor of variegation, increased both substantially. We discuss the possibility that changes in replication alter copy number locally and also propose an alternative model of position-effect variegation based on the somatic elimination of heterochromatic sequences.